Supply Chain Management at Cattle Feedlot Company PT Agrisatwa Jaya kencana by using Soft Systems Methodology - Amalia, Zeika Deina (Journal of Business and Management, 2017)
Abstract. In recent years, the prices of beef in Indonesia keep rising and never went down to the formerly prices. These situations happen caused by high demand from the society while the domestic cattle supply is insufficient. As the implication, the price of beef in the market is soaring. Many factors that make this situation happens, there are inadequate supply facilities, lack of knowledge about breeding, inadequate breeding technology and also quota import regulation. Quota import regulation is one of government program to realizing Beef Self-Sufficiency Program in 2014 (PSDS/2014). The purpose is to increasing the amount of domestic cattle and reduces the number of cattle import. Methodology that used to do this research is soft systems methodology. Data collection gathered from primary and secondary data. Primary data are taken by interviewing employees, observation and document collection related to PT Agrisatwa Jaya Kencana. Secondary data are gathered from website of ministry of agriculture, ministry of trade, secretariat cabinet of Indonesia, Gabungan Pelaku Usaha Peternakan Sapi Potong Indonesia (GAPUSPINDO), Central Bureau of Statistics (BPS), and databoks. According to analysis that has been done, quota import regulation that implement on 2014 inflict to reduction number of cattle import PT Agrisatwa Jaya Kencana on 2015. It makes the company have to prepare strategies to face this situation. Some of company strategies are by non-activated temporary workers and searching for local cattle to safe the stock. This research offered four desirable and feasible improvements to increase effectiveness of company performance. They are makes warehouse condition check sheet, design Key Performance Indicator, invite cattle feedmill expert, and makes beef quality check sheet.Keywords: Feedlot company, qualitative research, quota import regulation, and soft systems methodology supply chain management